Some practices from STEM education and the incorporation of some SDG goals in the educational process in the Republic of North Macedonia - Jashari, Hasime (European Journal of Social Science Education and Research, 2023)
Interdisciplinary integration as a form of STEM(Sience, technology, engineering, mathematics) education including the combined learning of natural sciences, technology, engineering and mathematics has recently evoked interest in the involvement of this type of education to a greater extent in the educational process. STEM education still does not have the right approach in primary and secondary schools in the Republic of North Macedonia, so we will try to share some practices from working with our students. STEM education has developed with more intensity in our school since the implementation of the project ‘21st century Schools’ supported by the British Council. During this study, the activities were carried out during the academic year 2022/2023 in two primary schools in two different municipalities, namely in Ismail Qemali primary school in Nerasht village, Tearca municipality and in Simçe Nastovski primary school in Vratnica, Jegunovci municipality. As a result of the application of integrated methods in the educational process, students have shown the highest results in terms of the level of knowledge and skills obtained. In the application of the integrated methods, 250 students from two primary schools were involved, where 50 of them were active participants of the Ismail Qemali Coding Club.